2001
DOI: 10.1109/22.903094
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the kink phenomenon of transistor scattering parameter S/sub 22/

Abstract: In this paper, we investigate a new rectangular-fed printed open-slot antenna (POSA) with reflector, which has the advantages of improved radiation-pattern properties along with broad-bandwidth characteristics. The measured bandwidth of the proposed POSA with reflector is approximately 47.6% (Ϫ10 dB Ն S 11 ), thus, it can be used for PCS, DCS, and IMT-2000. But the measured bandwidth of the PCSA with reflector is approximately 46% (with VSWR Յ 2.0). The tilt angle at maximum gain is enhanced by using a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 1 publication
2
68
0
Order By: Relevance
“…In addition, we also found that the decrease of the measurement temperature and the increase of the device's width enhanced the kink effect of both S 11 and S 22 (not shown here). The enhancement of the kink phenomenon in the above three cases can be interpreted in terms of the increase of g m [11][12][13][14]. In addition, the enhancement of the kink phenomenon can also be interpreted in terms of poles and zeros [14,15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we also found that the decrease of the measurement temperature and the increase of the device's width enhanced the kink effect of both S 11 and S 22 (not shown here). The enhancement of the kink phenomenon in the above three cases can be interpreted in terms of the increase of g m [11][12][13][14]. In addition, the enhancement of the kink phenomenon can also be interpreted in terms of poles and zeros [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1(a)-(d) shows the four measured S parameters (S 11 , S 22 , S 12 , and S 21 ) of the RF-power n-MOSFET with 400-m total gate width at V DS ϭ 3 V and various gate-source voltages. The kink phenomena of the S 11 and S 22 of the RF-power MOSFETs can be explained by deriving the input and output impedances (or admittances), respectively, of a four-terminal MOSFET under the measurement conditions of the S parameters [11][12][13][14][15]. Our results show that the input impedance of the RF-power MOSFETs intrinsically shows a simple series-RC circuit at low frequencies and a "shifted" parallel-RC circuit at high frequencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (7) is the same formula used in [17,18] with no g o consideration. This proofs the robustness of the formulation.…”
Section: The Impedance Zmentioning
confidence: 99%
“…However, for the sake of model completeness for the transistor with larger g o , it is included in the formulation. In the case where Y π is much smaller than g m (with g o neglected), (3) will reduced to local series-series feedback concept shown in [13,17,18]. With some necessary circuit elements modification as in (3), emitter resistance is uncoupled.…”
Section: Simplified Unilateral and Miller Approximation Performancementioning
confidence: 99%